ANALISIS KETERLAKSANAAN PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LEARNING CYCLE 5E TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI MONERA KELAS X SMA IT AL-FITYAH PEKANBARU - Nahdhah Amaliyah; Yuslim Fauziah; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the applicability of using Student Worksheets (LKPD) based on learning cycle 5e on student learning outcomes in class X SMA IT Al-Fityah Pekanbaru's monera material. This research uses a qualitative descriptive method. This research was conducted at SMA IT Al-Fityah Pekanbaru in October-November 2022 with a sample of 26 students of class X SMA IT Al-Fityah Pekanbaru. Methods of data collection in the form of interviews, observation and documentation. Research instruments were in the form of learning tools consisting of syllabus, Lesson Plans (RPP), and Student Worksheets (LKPD) based on learning cycle 5e, and data collection instruments in the form of observation sheets and test questions on learning outcomes. The results of the analysis of the implementation of the use of LKPD based on learning cycle 5 were carried out well with a percentage of 50% in the first meeting, 65% in the second meeting, 77% in the third meeting and 85% in the fourth meeting with a very good category. While the learning outcomes obtained after using LKPD based on learning cycle 5e each meeting increased with a percentage of 81% in the first meeting, 84.61% in the second meeting, 88.46% in the third meeting and 92% in the fourth meeting. Based on these data it can be concluded that the use of LKPD based on learning cycle 5e is implemented well and can improve learning outcomes.Key Words: Learning Cycle 5e, Learning Outcomes, Student Worksheets (LKPD)